The Baltic and North Seas Climatology (BNSC)—A Comprehensive, Observation-Based Data Product of Atmospheric and Hydrographic Parameters - Hinrichs, Iris; Jahnke-Bornemann, Annika; Andersson, Axel; Ganske, Anette; Gouretski, Viktor; Jensen, Corinna; Klein, Birgit; Möller, Jens; Sadikni, Remon; Tinz, Birger (Frontiers in Earth Science, 2019)
The Baltic and North Seas Climatology (BNSC) presented here is a new climatology calculated solely from marine in situ observations. Created in cooperation between University of Hamburg (UHH), Federal Maritime and Hydrographic Agency [Bundesamt für Seeschifffahrt und Hydrographie (BSH)] and German Meteorological Service [Deutscher Wetterdienst (DWD)], the BNSC is an update of the KLIWAS(“Klimawandel und Wasserstraßen”) climatology for the North Sea and is extended to the Baltic Sea. A thorough quality control, the reduction of the temporal sampling error and spatial and temporal averaging were applied to the observations, yielding time series of gridded fields of atmospheric and hydrographic parameters in the region of the Baltic, the North Sea and adjacent regions of the North Atlantic. The atmospheric subset of the BNSC consists of time series of monthly mean gridded fields of 2 m air and dew point temperature and air pressure at sea level for the period 1950 to 2015 on a horizontal 1°x1° grid. Climatological fields are provided as well. The hydrographic part of the BNSC comprises the variables water temperature and salinity on 105 depth levels for the time interval 1873-2015. The grid boxes’ edge length is 0.25° in both zonal and meridional direction. Monthly and annual mean fields are provided as well as decadal monthly mean fields. To create homogenous fields, the method of objective analysis was applied to the fields of decadal means. Furthermore, an extensive sensitivity study was carried out to assess the sensitivity of the data product to the amount of observational data. The BNSC introduced here is compared to several different data products: three reanalyses (ERA-Interim, ERA-40 and COSMO-REA6), the corresponding KLIWAS product and meteorological station data for the atmospheric part. The hydrographic subset is compared to the KLIWAS climatology, the BALTIC ATLAS and the Baltic Sea Physical Reanalysis Product. The BNSC data product allows studying of climate variability but also holds the chance to validate regional numerical climate simulations, which makes it a valuable reference data set. The BSNC is freely available via the website of University of Hamburg’s Integrated Climate Data Center.